Current Status of Chickpea Ascochyta Blight in Turkey - ÖZYİĞİT, İBRAHİM İLKER (My University, 2015)
Introduction: Turkey is one of the leading chickpea producing country in the world and origin center of chickpea cultivation dating back 10.000-12.000 years (Lev-Yadun et al., 2000). Ascochyta blight and Fusarium wilt are major diseases that severely restrict chickpea cultivation in Turkey (Kaiser and Kusmenoglu, 1997; Demirci et al., 1999). To perform and breed resistant/tolerant chickpea cultivars against Ascochyta blight, it is necessary to define population structure of Didymella rabiei in our country. Objectives: This study was undertaken to explore Ascochyta blight incidence, mating type distribution and virulence variations of D. rabiei in the chickpea growing areas of Turkey. Materials and methods: Survey studies to chickpea fields were conducted in 47 chickpea growing provinces covering seven regions of Turkey in 2013-2014 growing season. Altitudes, GPS locations, Fusarium wilt occurrence, weed coverage, nodulation and vegetation data’s were also collected for each filed. A total of 806 (19.536 da) chickpea fields were evaluated and disease incidences were calculated according to Reddy and Singh (1984). Mating types of over 250 D. rabiei isolates were analyzed using SP21, COM1 and Tail 5 primers through PCR (Barve et al., 2003). Pathotyping of selected isolates were determined according to Udupa et al., (1998). Results: The highest disease incidence was observed in the Bosporus region with %40.11 and followed by Black Sea, Aegean, Central Anatolia, Mediterranean, Southeastern and Eastern regions of Turkey. Disease incidence exhibited negative correlation with elevation (r= -,314; p<,001) and nodulation (r= -,076; p<,05). Mat1.1/Mat1.2 ratio was close to 1/1 but differences were observed among regions and provinces. Pathotypes 1, 2, 3, and 4 were detected in all the regions but Pathotype 4 was excessive in amount in institutes where chickpea breeding is being conducted for several years. Conclusion: Ascochyta blight caused by D. rabiei was determined to be common and predominant over Fusarium wilt in chickpea growing provinces in Turkey. However, Fusarium wilt was detected to be an emerging disease in the Aegean, Mediterranean and Bosporus regions. Occurrence of Pathotype 4 which is a highly virulent group of D. rabiei (Imtiaz et al., 2011) was first determined in Turkey through this study. This study was supported by The Scientific and Technological Research Council of Turkey (TÜBİTAK) with project number 113O071
Keywords: Temel Bilimler; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary